2016
DOI: 10.1080/02791072.2015.1130885
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Antisocial and Borderline Features and Aggression in Young Adult Men in Treatment for Substance Use Disorders

Abstract: There is a large literature documenting that adult men in treatment for substance use disorders perpetrate more aggression than men without substance use disorders. Unfortunately, there is minimal research on aggression among young adult men (i.e., 18–25 years of age) in treatment for substance use. Moreover, although aggression is more likely to occur when individuals are acutely intoxicated by alcohol or drugs, research also suggests that antisocial (ASPD) and borderline (BPD) personality features increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
1
3
0
2
Order By: Relevance
“…Our findings show that accuracy of prediction of future violent recidivism among offenders with impulsive tendencies was fair, using both the IMP‐V scores and the categorical summary risk ratings. The AUC values obtained were in line with studies showing a robust association between impulsivity and aggression in men with features of antisocial and/or borderline personality disorders and in extremely violent criminals (Shorey, Elmquist, Anderson, & Stuart, ; Værøy, Western, & Andersson, ). Affective dysregulation or instability and a tendency to act out, because of inability to control and modulate one's affective state when in state of heightened affect is also found in antisocial and narcissistic personality disorders (Chapman, Leung, & Lynch, ; Roussos & Siever, ; Shedler & Westen, ).…”
Section: Discussionsupporting
confidence: 88%
“…Our findings show that accuracy of prediction of future violent recidivism among offenders with impulsive tendencies was fair, using both the IMP‐V scores and the categorical summary risk ratings. The AUC values obtained were in line with studies showing a robust association between impulsivity and aggression in men with features of antisocial and/or borderline personality disorders and in extremely violent criminals (Shorey, Elmquist, Anderson, & Stuart, ; Værøy, Western, & Andersson, ). Affective dysregulation or instability and a tendency to act out, because of inability to control and modulate one's affective state when in state of heightened affect is also found in antisocial and narcissistic personality disorders (Chapman, Leung, & Lynch, ; Roussos & Siever, ; Shedler & Westen, ).…”
Section: Discussionsupporting
confidence: 88%
“…It is not unusual to find modest results of R/S mediation analysis [ 44 , 45 ], probably because of the complexity of this multidimensional concept. We suggest further investigation of other mental health disorders as possible mediators of R/S and violence, such as antisocial and borderline personality disorders, which can be associated with more aggressive behaviors [ 46 ]. Furthermore, interventional methodological designs to reduce aggressive and criminal behavior have been showing satisfactory results [ 43 , 47 ] and should be considered when exploring possible mechanisms of action of the R/S dimension.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborated by previous findings, which showed that heavy episodes of drinking mediated the protective effect of church attendance on sexual aggression in a follow-up period of 2 years in university students [22] and by a study that showed that discussing spiritual/moral values to partners, victims and perpetrators of domestic violence, resulted in a 71% reduction in the cases of violence [43] It is not unusual to find modest results of R/S mediation analysis [44,45], probably because of the complexity of this multidimensional concept. We suggest further investigation of other mental health disorders as possible mediators of R/S and violence, such as antisocial and borderline personality disorders, which can be associated with more aggressive behaviors [46]. Furthermore, interventional methodological designs to reduce aggressive and criminal behavior have been showing satisfactory results [43,47] and should be considered when exploring possible mechanisms of action of the R/S dimension.…”
Section: Plos Onementioning
confidence: 93%
“…Although the overwhelming majority of studies in this field demonstrate that ASPD and substance abuse both contribute to aggression, contrasting findings also exist. For instance, a study by Shorey et al showed that aggressive behavior was not associated with alcohol or substance abuse in patients with ASPD 30 .…”
Section: Discussionmentioning
confidence: 99%